A Taxonomy of Organizational Justice Theories - Greenberg, Jerald (Academy of Management Review, 1987)
A taxonomy is presented that categorizes theories of organizational justice with respect to two independent dimensions: a reactiveproactive dimension and a process-content dimension. Various theories within each of the four resulting categories are identified. The implications of the taxonomy are discussed with respect to clarifying theoretical interrelationships, tracking research trends, and identifying needed areas of research. Stimulated by conceptualizations of justice in organizations by such theorists as Homans (1961), Adams (1965), and Walster, Berscheid, and Walster (1973), organizational researchers devoted considerable attention in the 1960s and 1970s to testing propositions about the distribution of payment and other work-related rewards derived from equity theory (for reviews, see Campbell &